Comparative study of the biomechanical characteristics of landings performed at vault - Gavojdea, A. M. (Science, Movement & Health, 2015)
Aim: Landing in modern gymnastics is one of the most important factors which determine the final rank of gymnasts at competitions. The main purpose of this paper is to highlight and compare the characteristics of landings performed at vault, at level 4 gymnasts, age 12-13 years old. Methods: The study was conducted at the Juniors Individual National Championships, One.ti 2013 and Deva 2014. The study`s subjects were three level 4 gymnasts, vault finalists, in the two championships. The study analysed 12 landings. Each one of the gymnasts performed two vaults at each championship. These were biomechanically analysed and then compared. The comparative study was conducted both between all the gymnasts vaults, and between each one`s vaults, individually. The research methods used in the study were: bibliographical study, observation method, biomechanical video analysis method and statistical and graphic representation method. Results: By analysing all the vaults, we observe that the flyght`s lenght was shorter in 2014 (PF1=1,50m), compared with 2014 (1,91m), althrough the flyght`s heigh wasn`t higher (0,43m in 2013 and 0,28m in 2014). The horisontal displacement of body segments shows that also the two phases of the landing was higher in 2014 (PF1=1,50m and PF2=1,93m), compared with 2013 (PF1=1,91m and PF2=2,23m). The results of the sports performances obtained in competition and the landings penalties, highlights an final average mark of 13,43 points in the apparatus finals in 2013, a decrease of final average of 0,40 points in 2014 (13,03 points). The same difference of 0,40 points was also recorded between the landings penalties at both competitions (1,60 points in 2013 and 2,00 points in 2014). Conclusions: The biomechanical study of the landings performed at vault highlights that the gymnasts don`t master the landings, doing execution mistakes and losing important points. Therefore, we consider that there is necessary to perform a training program of landings.